CSS : the definitive guide : web layout and presentation - Meyer, Eric A.; Weyl, Estelle (Sebastopol, CA : O'Reilly Media, 2023)
If you're a web designer or app developer interested in sophisticated page styling, improved accessibility, and less time and effort expended, this book is for you. This revised fifth edition provides a comprehensive guide to CSS implementation along with a thorough review of the latest CSS specifications. Authors Eric Meyer and Estelle Weyl show you how to improve user experience, speed development, avoid potential bugs, and add life and depth to your applications through layout, transitions and animations, borders, backgrounds, text properties, and many other tools and techniques. They read the specs so you don't have to!
Includes bibliographical references and index.
Keywords: Cascading style sheets; Web sites -- Design; Feuilles de style en cascade; Sites Web -- Conception